A pilot randomized controlled trial of omega‐3 fatty acid supplementation for the treatment of anxiety in adolescents with anorexia nervosa. Issue 12 (26th October 2018) - Manos, Brittny E.; Bravender, Terrill D.; Harrison, Tondi M.; Lange, Hannah L. H.; Cottrill, Casey B.; Abdel‐Rasoul, Mahmoud; Bonny, Andrea E.
Abstract: Objective: To evaluate the effectiveness and tolerability of omega‐3 polyunsaturated fatty acid (PUFA) supplementation for treatment of trait anxiety among adolescent females with restrictive anorexia nervosa (AN). Method: A pilot double‐blind, placebo‐controlled randomized trial of adolescent females with AN ( N  = 24) entering Partial Hospitalization Program (PHP) from January 2015 to February 2016. Participants were randomized to four daily PUFA (2, 120 mg eicosapentaenoic acid/600 mg docosohexaenoic acid) or placebo capsules for 12 weeks. A 9‐item questionnaire of side effect frequency assessed medication tolerability. The Beck Anxiety Inventory‐Trait measured anxiety at baseline, 6, and 12 weeks. Linear mixed models evaluated associations between randomization group and study outcomes. Twenty‐two and 18 participants completed 6 and 12 weeks of data collection, respectively. Results: Medication side effect scores were low and were not significantly different between randomization groups at Week 6 ( p  = .20) or 12 ( p  = .41). Mean trait anxiety score significantly ( p  < .01) decreased from baseline to 12 weeks in both groups, and the rate of change over the course of time did not differ between omega‐3 PUFA and placebo groups ( p  = .55). Conclusion: Omega‐3 PUFA supplementation was well tolerated in adolescent females with AN. Although power to detect differences was limited, we found no evidence that omega‐3 PUFA benefited anxiety beyond nutritional restoration.